LITERASI INFORMASI MASYARAKAT DESA TANJUNG DAYANG UTARA, KECAMATAN INDRALAYA SELATAN, KABUPATEN OGAN ILIR MELALUI BUDAYA WARUNG - Iswara, Dwi Fuji; Rohmaniyah, Rohmaniyah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
The purpose of this study was to describe and analyze the factors underlying the formation of roadside stall culture and information literacy. The research method used qualitative research method. The data collection technique used was observation, interviews, and documentation. The result of this study showe roadside stall culture was formed based on the history of the village community to set strategies of defending themselves from Dutch colonialism by creating gathering habits. After the Dutch colonial period ended, this gathering habit became attached to the village community. The ‘ warung’ was considered the most strategic place for gathering. This place can accommodate all people from various backgrounds to chat, have fun, establish silaturahmi/hospitality, relax from daily activities, and get the information needed. Roadside stall culture fulfills four cultural systems, namely: culture, social, personality, and organism. Roadside stall culture is very closely related to information literacy and Hubermas' theory of public space. The Tanjung Dayang Utara village community has implemented the IFLA information literacy standard in supporting its work, from the access, evaluation, to usage stages.